A kind of hydrogen peroxide high-efficiency water treatment agent and its preparation process

By adopting a combined water treatment agent of composite microspheres and modified copolymers, the problem of being unable to efficiently adsorb heavy metals and remove complex organic wastes in the prior art is solved, and efficient removal of various pollutants in industrial wastewater and water treatment is achieved. Effect.

CN119080136BActive Publication Date: 2025-02-14GAOMI JIANTAO CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411569761.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

In the prior art, hydrogen peroxide cannot efficiently adsorb heavy metal impurities when used as a water treatment agent, and modified inorganic adsorption materials cannot effectively remove complex organic waste in industrial wastewater.

Method used

Using a combined water treatment agent of composite microspheres and modified copolymers, the composite microspheres are prepared from silica gel, hydrogen peroxide-modified activated carbon powder and iron tetraoxide emulsified cross-linking. The modified copolymer is made of methyl fumarate, Maleic anhydride, hydrothermal treatment of lignin mixture and esterification products are obtained by copolymerizing.

Benefits of technology

It realizes efficient adsorption and decomposition of heavy metal ions in industrial wastewater, reduces the content of harmful substances and organic substances of ammonia nitrogen, and improves the adsorption and catalytic properties of water treatment agents.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a hydrogen peroxide high-efficiency water treatment agent and a preparation process thereof, and belongs to the technical field of water treatment agents. The present invention is used to solve the problem that when hydrogen peroxide is used as a water treatment agent to treat chemical industrial wastewater in the prior art, heavy metal impurities therein cannot be efficiently adsorbed; when inorganic adsorption materials modified by hydrogen peroxide are used as water treatment agents, various organic wastes in industrial wastewater cannot be efficiently adsorbed. The hydrogen peroxide high-efficiency water treatment agent prepared by the present invention comprises composite microspheres and modified copolymers; the composite microspheres are obtained by emulsifying and cross-linking silica gel and activated carbon powder modified by hydrogen peroxide; the modified copolymer is obtained by copolymerizing methyl fumarate, maleic anhydride, a lignin mixed solution after hydrothermal treatment, and an esterification product. The water treatment agent prepared by the present invention can remove heavy metal ions and organic pollutants in industrial wastewater, and has the advantages of high adsorption efficiency and green environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment agents, and in particular to a hydrogen peroxide high-efficiency water treatment agent and a preparation process thereof. Background Art

[0002] The fine chemical industry plays an important role in my country's national economy. With the accelerated development of industrialization, the demand for various fine chemicals has increased year by year, which has promoted the vigorous development of the industry; however, the environmental pollution caused by the fine chemical industry cannot be ignored. On the one hand, the raw materials used in fine chemical production are mostly organic poisons such as chlorinated hydrocarbons, brominated hydrocarbons, aromatic compounds, alcohols, acids and ketones. These substances are highly toxic and difficult to degrade. On the other hand, the fine chemical production process is complicated, which will lead to a large amount of raw materials, intermediates and by-products being discharged in the form of "three wastes". This type of wastewater has a high content of heavy metal ions and is one of the more difficult industrial wastewaters to treat.

[0003] Hydrogen peroxide is a strong oxidant that can disinfect and purify cyanide and sulfide, and remove harmful substances such as organic acid salts, phenols, aldehydes, esters, etc. in wastewater. When hydrogen peroxide is used as a wastewater treatment agent, it only produces oxygen and water when it decomposes, without secondary pollution. With the increasing awareness of environmental protection, hydrogen peroxide will be more widely used as a water treatment agent in fine chemical wastewater. However, hydrogen peroxide cannot adsorb high-content metal ions in industrial wastewater. Using hydrogen peroxide to modify the prepared water treatment agent to further improve its adsorption efficiency is another application idea.

[0004] Patent application CN109928474A discloses a method and application of preparing polyferric sulfate from waste sulfuric acid containing o-cyano-p-nitroaniline. Polyferric sulfate is synthesized by hydrogen peroxide oxidation, waste acid is added in a two-step method, and hydrogen peroxide is added under the liquid surface to obtain polyferric sulfate as a water treatment agent. Polyferric sulfate can flocculate with suspended matter and colloidal substances in water and precipitate to obtain flocs. However, polyferric sulfate cannot chemically decompose harmful substances such as phenolic aldehydes and halogenated hydrocarbons in industrial wastewater.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a hydrogen peroxide high-efficiency water treatment agent and a preparation process thereof, which are used to solve the technical problems in the prior art that when hydrogen peroxide is used as a water treatment agent, heavy metal impurities therein cannot be efficiently adsorbed; and when an inorganic adsorption material modified by hydrogen peroxide is used as a water treatment agent, complex organic wastes in industrial wastewater cannot be efficiently adsorbed.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A hydrogen peroxide high-efficiency water treatment agent, comprising the following components in parts by weight: 5-8 parts of composite microspheres and 10 parts of modified copolymers;

[0009] The composite microspheres are obtained by emulsifying and cross-linking silica gel, activated carbon powder modified by hydrogen peroxide and ferrosoferric oxide;

[0010] The preparation method of the composite microspheres comprises the following steps:

[0011] B1, silica gel and deionized water are mixed and ultrasonically treated to obtain a mixed suspension;

[0012] Silica gel and deionized water were mixed as the aqueous phase;

[0013] B2, add hydrogen peroxide modified activated carbon powder to the mixed suspension, mix once and mix evenly; then add ferroferric oxide and mix twice and mix evenly; then add liquid paraffin and Span 80 to obtain a mixed solution B; the mixed solution B reacts at 40-50° C. for 3-4 hours, then adds a crosslinking agent glutaraldehyde to carry out a crosslinking reaction for 2-3 hours to obtain an emulsified crosslinked mixed solution;

[0014] The activated carbon is added into liquid paraffin containing surfactant as the oil phase; ferroferric oxide is used as the doping metal to obtain an oil-in-water emulsifier; and a cross-linking agent is added to fully cross-link the base silica gel and the activated carbon powder modified by hydrogen peroxide.

[0015] B3, filtering the emulsified cross-linked mixed solution, washing it three times with anhydrous ethanol, and then freeze-drying it to obtain composite microspheres;

[0016] The emulsified cross-linked mixed solution is subjected to post-processing to obtain composite microspheres.

[0017] B4, mixing the composite microspheres and the modified copolymer evenly to obtain a hydrogen peroxide high-efficiency water treatment agent;

[0018] The modified copolymer is obtained by copolymerizing methyl fumarate, maleic anhydride, a hydrothermally treated lignin mixed solution and an esterification product, wherein the esterification product is obtained by an esterification reaction of acrylic acid monomer and allyl polyoxyethylene ether.

[0019] Furthermore, the preparation method of the modified copolymer comprises the following steps:

[0020] A1. The reactor is equipped with a thermometer, a stirring blade, a titration device and an oil-water separator; acrylic acid monomer, allyl polyoxyethylene ether, an inhibitor and a catalyst are added into the reactor, and then the reactor is heated to 110-150°C, and an esterification reaction is carried out under reflux for 3-6 hours to obtain an esterification product; during the esterification reaction, water generated by the reaction is received from the outlet at the bottom of the oil-water separator of the reactor;

[0021] Allyl polyoxyethylene ether and acrylic acid monomer undergo esterification reaction to obtain an esterification product; in the actual production process, an oil-water separator is used to promptly remove the water generated by the reaction, thereby promoting the forward progress of the esterification reaction.

[0022] The acrylic acid monomer reacts with allyl polyoxyethylene ether to obtain the esterification product as follows:

[0023] ;

[0024] The number average molecular weight of allyl polyoxyethylene ether is 2,000.

[0025] A2. Dissolve the initiator in deionized water to obtain an initiator solution; cool the reactor naturally to room temperature, add methyl fumarate, maleic anhydride and a mixed solution of hydrothermally treated lignin to the above esterification product, mix and mix well to obtain a mixed monomer liquid; then drop all the initiator solution into the mixed monomer liquid; after the dropwise addition is completed, carry out a heat-insulating reaction at 80-90° C. for 3-6 hours, and then cool naturally to room temperature to obtain a mixed solution A; the mixed solution A is subjected to a post-process treatment to obtain a modified copolymer.

[0026] Under the action of ammonium persulfate initiator, methyl fumarate, double bonds in maleic anhydride and esterification products undergo addition polymerization to obtain a copolymer.

[0027] The reaction formula for the addition reaction of methyl fumarate, maleic anhydride and the esterification product is as follows:

[0028] ;

[0029] Furthermore, in step A1, the inhibitor is hydroquinone and the catalyst is p-toluenesulfonic acid; the amounts of acrylic acid monomer, allyl polyoxyethylene ether, inhibitor and catalyst are 20-30g: 50-60g: 0.15-0.2g: 1.5-2g.

[0030] Furthermore, in step A2, the initiator is ammonium persulfate, and the amount of the initiator and deionized water is 5-10g:50mL; the amount ratio of methyl fumarate, maleic anhydride and the lignin mixed solution after hydrothermal treatment is 10-15g:10-20g:20-30mL; the post-process treatment is: adding NaOH solution to the reactor and adjusting the pH value of the mixed solution to 7-9.

[0031] Furthermore, in step A2, the method for preparing the hydrothermally treated lignin mixed solution comprises the following steps:

[0032] The lignin fiber is ground to obtain lignocellulose powder; 30-50g of lignocellulose powder and 500g of distilled water are added into a reactor, and the pressure value of the reactor is set to 0.15-0.25MPa; the reactor is heated from room temperature to 190-200°C, and then kept at this temperature for 30-60min to obtain a hydrothermally treated lignin mixed solution.

[0033] Under high temperature and high pressure conditions, the lack of tetrahedral coordination in liquid water causes the hydrogen network structure of water to be broken, increasing the rate of water self-diffusion movement; at high temperature, the ionization constant of liquid water increases, and the ionized H + and OH - The ion concentration is higher than that of ambient liquid water. Therefore, water has the function of acid-base autocatalysis at high temperature. Lignocellulose is mainly composed of three parts: cellulose, hemicellulose and lignin. Lignin is treated by hydrothermal method, and the glycosidic bonds, O-acetyl groups and O-uronic acid groups of hemicellulose are hydrolyzed to generate organic acids such as acetic acid, uronic acid, oligoxylose and arabinose. Both cellulose and lignin are rich in hydroxyl functional groups, so that each component of lignocellulose can react with the anhydride groups in maleic anhydride to obtain modified copolymers.

[0034] Furthermore, in step B1, the usage ratio of silica gel and deionized water is 2-5 g:20-30 mL; the frequency of ultrasonic treatment is 20-30 KHz; in step B2, the usage ratio of hydrogen peroxide-modified activated carbon powder, ferrosoferric oxide, liquid paraffin, Span 80 and glutaraldehyde is 5-10 g:0.2-0.5 g:20 mL:1-2 g:2-5 mL.

[0035] Furthermore, in step B2, the hydrogen peroxide-modified activated carbon powder is prepared by the following steps:

[0036] The activated carbon is ball-milled to obtain activated carbon powder; the activated carbon powder and hydrogen peroxide solution are mixed for reaction at a reaction temperature of 60-70°C for a reaction time of 2-3 hours, and then filtered to obtain hydrogen peroxide-modified activated carbon powder.

[0037] Furthermore, the ball milling speed is 100-200 r / min, the ball milling time is 1-2 h; and the dosage ratio of activated carbon powder and hydrogen peroxide solution is 5-10 g:20 mL.

[0038] The present invention has the following beneficial effects:

[0039] 1. The water treatment agent prepared by the present invention is obtained by mixing composite microspheres and modified copolymers. Silica gel and activated carbon modified by hydrogen peroxide are used as basic raw materials, a small amount of ferroferric oxide is added, and a cross-linking agent is used as an intermediate medium. Composite microspheres of silica gel-hydrogen peroxide modified activated carbon-ferroferric oxide structure are prepared by emulsification cross-linking method. The inner-outer multi-layer highly porous structure can provide a higher specific surface area for the composite microspheres, thereby achieving efficient and continuous adsorption of heavy metal elements. Silica gel has a mesoporous structure. At normal density, the specific surface area of ​​silica gel is 750-850m 2 / g, and the average pore diameter is 22-25Å. Silica gel itself is an amorphous adsorption material, and by compounding with activated carbon, a tangible composite microsphere is obtained. The activated carbon used in the present invention can be applied as liquid phase adsorption activated carbon, and the pore diameter of most of its pores is close to or greater than 30Å; its pore size distribution has various forms, and the large pores are called supply pores or transmission pores, which run through the entire surface of the activated carbon particles; there are many small pores branching from the large pores, which are also called adsorption pores. The specific surface area of ​​activated carbon is large, and the activated carbon modified by hydrogen peroxide can further increase its specific surface area and increase the number of holes; in addition, when the activated carbon modified by hydrogen peroxide is emulsified and cross-linked with silica gel, the silica gel can be hydrolyzed by hydrogen peroxide to form silica acid. The hydroxyl group attached to silica acid increases its own reaction with the cross-linking agent, thereby increasing the cross-linking density and stability of the prepared composite microspheres. In addition, a single inorganic adsorption material is always affected by pH and temperature, which limits its application in water treatment. The preparation of composite inorganic microspheres can not only maximize the performance of a single component, but also enable the components to produce a synergistic effect.

[0040] 2. Another active component in the water treatment agent prepared by the present invention is specifically a modified copolymer; the molecular structure of the modified copolymer is comb-shaped, and polar groups such as carboxyl, anhydride, aldehyde, and hydroxyl are carried on the main chain. The multi-active functional groups of the side chain are used to improve the adsorption performance of the prepared modified copolymer. In addition, the side chains of the molecule can form a spatial barrier through electrostatic repulsion and electrostatic adsorption, which helps to adsorb impurities to form agglomerates. Acrylic acid monomer and allyl polyoxyethylene ether are subjected to esterification reaction to obtain an esterified monomer; the esterified monomer, methyl fumarate and maleic anhydride are used as monomers, and the main chain of the copolymer is obtained through addition reaction. Among them, methyl fumarate, as an antibacterial substance, can inhibit a variety of bacteria and yeasts, so that the prepared modified copolymer has antibacterial properties. In addition, the present invention uses hydrothermally treated wood cellulose as a functional monomer to improve the adsorption performance of the copolymer. After hydrothermal treatment, lignin can expose a large number of active functional groups, which can undergo physical effects of van der Waals forces and electrostatic attraction and chemical effects of surface complexation with various polar groups in the side chains of the copolymer. The above-mentioned modified products have green and environmentally friendly effects and can reduce the production cost of preparing water treatment agents.

[0041] 3. The composite microspheres used in the hydrogen peroxide efficient water treatment agent prepared by the present invention can efficiently adsorb heavy metal ions in industrial wastewater. The small amount of ferroferric oxide contained in the composite microspheres can decompose the harmful substances of ammonia nitrogen contained in the industrial wastewater and reduce the organic content in the industrial wastewater. Due to the high surface energy of the ferroferric oxide particles, particles are very likely to agglomerate with each other, thereby greatly reducing the surface active sites, thereby affecting their own adsorption performance. The present invention distributes ferroferric oxide in the silica gel and activated carbon of the inner and outer layers, thereby reducing the agglomeration of ferroferric oxide and improving its own dispersibility. On the other hand, the modified copolymer used in the hydrogen peroxide efficient water treatment agent prepared by the present invention can react chemically through the rich functional groups contained in the side chain, effectively removing organic poisons such as chlorinated hydrocarbons and brominated hydrocarbons in industrial wastewater. The composite microspheres and the modified copolymer are compounded according to a certain ratio, and the prepared hydrogen peroxide efficient water treatment agent can achieve efficient removal of various impurities in industrial wastewater through various ways such as physical adsorption and chemical reaction. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] The wood cellulose used in Examples 1-3 of the present invention was purchased from Jiayuan Mineral Products Processing Plant in Lingshou County, and the raw material was poplar wood; the silica gel used in Examples 4-6 of the present invention was model 112926-00-8, and the molecular weight was 60.08; the activated carbon used in Examples 4-6 of the present invention was columnar wood activated carbon, purchased from Liyang Zhucai Environmental Protection Technology Co., Ltd., model 005.

[0044] Example 1

[0045] This embodiment provides a method for preparing a modified copolymer for a hydrogen peroxide high-efficiency water treatment agent, comprising the following steps:

[0046] A1. Grind the cellulose with a grinder to obtain 50-mesh cellulose powder; add 30 g of cellulose powder and 500 g of distilled water into a 1 L reactor; set the reactor pressure to 0.15 MPa, heat the reactor from room temperature to 190 ° C at 5 ° C / min, and then keep it at this temperature for 30 minutes to obtain a hydrothermally treated lignin mixed solution.

[0047] A2. Select a 250mL experimental reactor equipped with a thermometer, a stirring paddle, a titration device and an oil-water separator. Add 20g of acrylic acid monomer, 50g of allyl polyoxyethylene ether, 0.15g of inhibitor hydroquinone and 1.5g of catalyst p-toluenesulfonic acid into the laboratory reactor, then heat the laboratory reactor to 110°C, adjust the stirring rate of the stirring paddle to 1000r / min, and carry out the esterification reaction for 3h under reflux to obtain an esterified product; during the esterification reaction, receive the water generated by the reaction from the outlet at the bottom of the oil-water separator of the reactor.

[0048] A3. Dissolve 5g of initiator ammonium persulfate in 50mL of deionized water to obtain an initiator solution. Cool the reactor naturally to room temperature, add 10g of methyl fumarate, 20g of maleic anhydride and 20mL of hydrothermally treated lignin mixture, mix evenly with a stirring paddle to obtain a monomer mixture. Then, through the titration device in the reactor, add all the initiator solution to the reactor at a rate of 1mL / min. After the addition is completed, the reactor is heated to 80°C, and the reaction is kept warm at this temperature for 3h, and then naturally cooled to room temperature to obtain a mixed solution A. Then, 0.1mol / L NaOH solution is added to the reactor at a rate of 1mL / min, and the pH value of the mixed solution A is adjusted to 7 to obtain a modified copolymer.

[0049] Example 2

[0050] This embodiment provides a method for preparing a modified copolymer for a hydrogen peroxide high-efficiency water treatment agent, comprising the following steps:

[0051] A1. Grind the cellulose with a grinder to obtain 20-mesh cellulose powder; add 40 g of cellulose powder and 500 g of distilled water into a 1 L reactor; set the pressure value of the reactor to 0.2 MPa, heat the reactor from room temperature to 195 ° C at 5 ° C / min, and then keep it at this temperature for 50 minutes to obtain a hydrothermally treated lignin mixed solution.

[0052] A2. Select a 250mL experimental reactor equipped with a thermometer, a stirring paddle, a titration device and an oil-water separator. Add 23g of acrylic acid monomer, 55g of allyl polyoxyethylene ether, 0.18g of inhibitor hydroquinone and 1.6g of catalyst p-toluenesulfonic acid into the laboratory reactor, then heat the laboratory reactor to 130°C, adjust the stirring speed of the stirring paddle to 1500r / min, and carry out the esterification reaction under reflux for 5h to obtain an esterified product; during the esterification reaction, receive the water generated by the reaction from the outlet at the bottom of the oil-water separator of the reactor.

[0053] A3. Dissolve 7g of initiator ammonium persulfate in 50mL of deionized water to obtain an initiator solution. Cool the reactor naturally to room temperature, add 12g of methyl fumarate, 15g of maleic anhydride and 25mL of hydrothermally treated lignin mixture, mix evenly with a stirring paddle to obtain a monomer mixture. Then, through the titration device in the reactor, add all the initiator solution to the reactor at a rate of 1mL / min. After the addition is completed, the reactor is heated to 82°C, and the reaction is kept warm at this temperature for 5h, and then naturally cooled to room temperature to obtain a mixed solution A. Then, 0.1mol / L NaOH solution is added to the reactor at a rate of 1mL / min, and the pH value of the mixed solution A is adjusted to 8 to obtain a modified copolymer.

[0054] Example 3

[0055] This embodiment provides a method for preparing a modified copolymer for a hydrogen peroxide high-efficiency water treatment agent, comprising the following steps:

[0056] A1. Grind the cellulose with a grinder to obtain 30-mesh cellulose powder; add 50 g of cellulose powder and 500 g of distilled water into a 1 L reactor; set the pressure value of the reactor to 0.25 MPa, heat the reactor from room temperature to 200 ° C at 5 ° C / min, and then keep it at this temperature for 60 minutes to obtain a hydrothermally treated lignin mixed solution.

[0057] A2. Select a 250mL experimental reactor equipped with a thermometer, a stirring paddle, a titration device and an oil-water separator. Add 30g of acrylic acid monomer, 60g of allyl polyoxyethylene ether, 0.2g of inhibitor hydroquinone and 2g of catalyst p-toluenesulfonic acid into the laboratory reactor, then heat the laboratory reactor to 150°C, adjust the stirring speed of the stirring paddle to 2000r / min, and carry out the esterification reaction for 6h under reflux to obtain an esterified product; during the esterification reaction, receive the water generated by the reaction from the outlet at the bottom of the oil-water separator of the reactor.

[0058] A3. Dissolve 10g of initiator ammonium persulfate in 50mL of deionized water to obtain an initiator solution. Cool the reactor naturally to room temperature, add 15g of methyl fumarate, 10g of maleic anhydride and 30mL of hydrothermally treated lignin mixed solution, mix evenly with a stirring paddle to obtain a monomer mixed solution. Then, through the titration device in the reactor, add all the initiator solution to the reactor at a rate of 1mL / min. After the addition is completed, the reactor is heated to 90°C, and the reaction is kept warm at this temperature for 6h, and then naturally cooled to room temperature to obtain a mixed solution A. Then, 0.1mol / L NaOH solution is added to the reactor at a rate of 1mL / min, and the pH value of the mixed solution A is adjusted to 9 to obtain a modified copolymer.

[0059] Example 4

[0060] This embodiment provides a preparation process of a hydrogen peroxide high-efficiency water treatment agent, comprising the following steps:

[0061] B1. Mix 2 g of silica gel and 20 mL of deionized water and add them into a 50 mL beaker. Transfer the beaker to an ultrasonic processor for ultrasonic treatment. The frequency of the ultrasonic treatment is 20 KHz and the duration of the ultrasonic treatment is 15 min to obtain a mixed suspension.

[0062] B2. The activated carbon was ball-milled with a planetary mill to obtain activated carbon powder; wherein the ball milling speed was 100 r / min and the ball milling time was 1 h. 5 g of activated carbon powder was mixed with 50 mL of 0.1 mol / L hydrogen peroxide solution for reaction at a temperature of 60°C for 2 h, and then filtered to obtain hydrogen peroxide-modified activated carbon powder.

[0063] B3. Add 5 g of hydrogen peroxide-modified activated carbon powder to the mixed suspension, and perform ultrasonic treatment at 20 KHz for 10 min to mix evenly. Then add 0.2 g of 50-mesh ferrosilicate, and perform ultrasonic treatment at 20 KHz for 10 min to mix evenly for a second time. Then add 20 mL of liquid paraffin and 1 g of Span 80 to obtain a mixed solution B. Transfer the beaker to an electric constant temperature drying oven, react at 40 ° C for 3 h, and then add 2 mL of a cross-linking agent glutaraldehyde for a cross-linking reaction for 2 h to obtain an emulsified cross-linked mixed solution.

[0064] B4. The emulsified cross-linked mixed solution was filtered, washed three times with anhydrous ethanol, and then freeze-dried for 24 hours to obtain composite microspheres.

[0065] B5. According to parts by weight, 5 parts of the composite microspheres and 10 parts of the modified copolymer prepared in Example 3 were mixed evenly to obtain a hydrogen peroxide water treatment agent.

[0066] Example 5

[0067] This embodiment provides a preparation process of a hydrogen peroxide high-efficiency water treatment agent, comprising the following steps:

[0068] B1. Mix 3 g of silica gel and 25 mL of deionized water and add them into a 50 mL beaker. Transfer the beaker to an ultrasonic processor for ultrasonic treatment. The frequency of the ultrasonic treatment is 25 KHz and the duration of the ultrasonic treatment is 18 min to obtain a mixed suspension.

[0069] B2. The activated carbon was ball-milled with a planetary mill to obtain activated carbon powder; wherein the ball milling speed was 150 r / min and the ball milling time was 1.3 h. 8 g of activated carbon powder was mixed with 50 mL of 0.1 mol / L hydrogen peroxide solution for reaction at a reaction temperature of 65° C. for a reaction time of 2.4 h, and then filtered to obtain hydrogen peroxide-modified activated carbon powder.

[0070] B3. Add 8 g of hydrogen peroxide-modified activated carbon powder to the mixed suspension, and perform ultrasonic treatment at 25 KHz for 15 min to mix evenly. Then add 0.3 g of 80-mesh ferrosoferric oxide, and perform ultrasonic treatment at 25 KHz for 15 min to mix evenly for a second time. Then add 20 mL of liquid paraffin and 1.6 g of Span 80 to obtain a mixed solution B. Transfer the beaker to an electric constant temperature drying oven, react at 45 ° C for 3.3 h, and then add 3 mL of a cross-linking agent glutaraldehyde for a cross-linking reaction for 2.5 h to obtain an emulsified cross-linked mixed solution.

[0071] B4. The emulsified cross-linked mixed solution was filtered, washed three times with anhydrous ethanol, and then freeze-dried for 24 hours to obtain composite microspheres.

[0072] B5. According to parts by weight, 6 parts of the composite microspheres and 10 parts of the modified copolymer prepared in Example 3 were mixed evenly to obtain a hydrogen peroxide water treatment agent.

[0073] Example 6

[0074] This embodiment provides a preparation process of a hydrogen peroxide high-efficiency water treatment agent, comprising the following steps:

[0075] B1. Mix 5 g of silica gel and 30 mL of deionized water and add them into a 50 mL beaker. Transfer the beaker to an ultrasonic processor for ultrasonic treatment. The frequency of the ultrasonic treatment is 30 KHz and the duration of the ultrasonic treatment is 20 min to obtain a mixed suspension.

[0076] B2. The activated carbon was ball-milled with a planetary mill to obtain activated carbon powder; wherein the ball milling speed was 200 r / min and the ball milling time was 2 h. 10 g of activated carbon powder was mixed with 50 mL of 0.1 mol / L hydrogen peroxide solution for reaction at a reaction temperature of 70°C for 3 h, and then filtered to obtain hydrogen peroxide-modified activated carbon powder.

[0077] B3. Add 10 g of hydrogen peroxide-modified activated carbon powder to the mixed suspension, and perform ultrasonic treatment at 30 KHz for 120 min to mix evenly. Then add 0.5 g of 100-mesh ferrosoferric oxide, and perform ultrasonic treatment at 30 KHz for 20 min to mix evenly for a second time. Then add 20 mL of liquid paraffin and 2 g of Span 80 to obtain a mixed solution B. Transfer the beaker to an electric constant temperature drying oven, react at 50 ° C for 4 h, and then add 5 mL of a cross-linking agent glutaraldehyde for a cross-linking reaction for 3 h to obtain an emulsified cross-linked mixed solution.

[0078] B4. The emulsified cross-linked mixed solution was filtered, washed three times with anhydrous ethanol, and then freeze-dried for 24 hours to obtain composite microspheres.

[0079] B5. According to parts by weight, 8 parts of the composite microspheres and 10 parts of the modified copolymer prepared in Example 3 were mixed evenly to obtain a hydrogen peroxide water treatment agent.

[0080] Comparative Example 1

[0081] Compared with Example 6, in this comparative example, a modified copolymer was prepared, and the lignin was not subjected to hydrothermal treatment to obtain a lignin mixed liquid.

[0082] Comparative Example 2

[0083] Compared with Example 6, in this comparative example, when preparing the hydrogen peroxide high-efficiency water treatment agent, the activated carbon was not activated by the hydrogen peroxide solution.

[0084] Comparative Example 3

[0085] Compared with Example 6, in this comparative example, ferrosoferric oxide was not added when preparing the composite microspheres, and then an equal mass of ferrosoferric oxide was added to the prepared hydrogen peroxide water treatment agent.

[0086] Performance Test:

[0087] 1. According to GB / T16632-2008 "Determination of scale inhibition performance of water treatment agents - calcium carbonate precipitation method", the scale inhibition performance of the hydrogen peroxide water treatment agents prepared in Examples 4-6 and Comparative Examples 1-3 on calcium carbonate scale and calcium sulfate scale was determined.

[0088] 2. Take 100 mL of industrial wastewater and place it in a 200 mL beaker. Use a spectrophotometer to measure the COD content and a turbidity meter to measure the turbidity. Then add 0.5 g of the hydrogen peroxide water treatment agent prepared in Examples 4-6 and Comparative Examples 1-3, stir mechanically at 300 r / min for 30 min to flocculate, let it stand for 30 min, and then measure the COD content and turbidity value. Then calculate the removal rate based on the COD content and turbidity value before and after treatment.

[0089] 3. Prepare a 200 mg / L heavy metal mixed solution (including copper ions, chromium ions and mercury ions), and add it to a conical flask; then weigh 50 mg of the hydrogen peroxide high-efficiency water treatment agent prepared in Examples 4-6 and Comparative Examples 1-3 and add them to the conical flask to obtain a reaction system, and adjust the pH value of the reaction system to 7. Then place the conical flask in a shaker to allow it to fully react for 24 hours, and use an atomic fluorescence analyzer to measure the heavy metal concentration after the reaction, and then calculate the removal rate. Each group of experiments was measured three times, and the average value was calculated. The calculation formula for heavy metal removal rate is as follows:

[0090] Heavy metal removal rate (%) = (concentration of heavy metal mixed solution before reaction - concentration of heavy metal mixed solution after reaction) / concentration of heavy metal mixed solution before reaction × 100%

[0091] Table 1. Sample performance test data

[0092] :

[0093] Data Analysis:

[0094] Analyzing the data in Table 1, the hydrogen peroxide water treatment agents prepared in Examples 4-6 of the present invention have excellent adsorption efficiency for organic matter and inorganic metal ions in industrial wastewater, and have excellent scale inhibition rates for calcium carbonate and calcium sulfate. However, in Comparative Example 1, the modified copolymer is prepared by replacing the lignin mixed solution after hydrothermal treatment with the lignin mixed solution. The lignocellulose is not hydrothermally treated, and various functional monomers are not decomposed. The number of active functional groups contained is small, which is manifested in a significant decrease in its own pollution inhibition efficiency and turbidity removal rate, and a decrease in heavy metal removal rate.

[0095] In Comparative Example 2, when preparing the hydrogen peroxide high-efficiency water treatment agent, the activated carbon was not activated by hydrogen peroxide solution; the specific surface area of ​​the activated carbon modified by hydrogen peroxide increased significantly, and hydrogen peroxide helped to hydrolyze silica gel, increase the crosslinking density of the composite microspheres, and help to improve the scale inhibition rate of calcium sulfate and calcium carbonate, turbidity removal rate and COD removal rate. The corresponding performance of the hydrogen peroxide high-efficiency water treatment agent prepared in Comparative Example 2 decreased.

[0096] In Comparative Example 3, when preparing the composite microspheres, ferroferric oxide was not added; then an equal amount of ferroferric oxide was added to the prepared hydrogen peroxide water treatment agent; the ferroferric oxide added later still played a role in catalytic oxidation and decomposition of harmful ammonia nitrogen substances in industrial wastewater. However, adding ferroferric oxide to the preparation of the composite microspheres will avoid the agglomeration of ferroferric oxide particles, thereby improving its own adsorption and catalytic efficacy. Therefore, the turbidity removal rate, COD removal rate and heavy metal removal rate of the hydrogen peroxide high-efficiency water treatment agent prepared in Comparative Example 3 were all reduced.

[0097] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0098] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0099] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A hydrogen peroxide high-efficiency water treatment agent, characterized in that: The invention comprises the following components in parts by weight: 5-8 parts of composite microspheres and 10 parts of modified copolymer; The composite microspheres are obtained by emulsifying and cross-linking silica gel, activated carbon powder modified by hydrogen peroxide and ferrosoferric oxide; The preparation method of the composite microspheres comprises the following steps: B1, silica gel and deionized water are mixed and ultrasonically treated to obtain a mixed suspension; B2, add hydrogen peroxide modified activated carbon powder to the mixed suspension, mix once and mix evenly; then add ferroferric oxide and mix twice and mix evenly; then add liquid paraffin and Span 80 to obtain a mixed solution B; the mixed solution B reacts at 40-50° C. for 3-4 hours, then adds a crosslinking agent glutaraldehyde to carry out a crosslinking reaction for 2-3 hours to obtain an emulsified crosslinked mixed solution; B3, filtering the emulsified cross-linked mixed solution, washing it three times with anhydrous ethanol, and then freeze-drying it to obtain composite microspheres; The composite microspheres and the modified copolymer are uniformly mixed to obtain a hydrogen peroxide high-efficiency water treatment agent; The modified copolymer is obtained by copolymerizing methyl fumarate, maleic anhydride, a hydrothermally treated lignin mixed solution and an esterification product, wherein the esterification product is obtained by an esterification reaction of acrylic acid monomer and allyl polyoxyethylene ether.

2. A hydrogen peroxide efficient water treatment agent according to claim 1, characterized in that: The preparation method of the modified copolymer comprises the following steps: A1. The reactor is equipped with a thermometer, a stirring blade, a titration device and an oil-water separator; acrylic acid monomer, allyl polyoxyethylene ether, an inhibitor and a catalyst are added to the reactor, and then the reactor is heated to 110-150° C., and an esterification reaction is carried out under reflux for 3-6 hours to obtain an esterification product; A2. Dissolve the initiator in deionized water to obtain an initiator solution; cool the reactor naturally to room temperature, add methyl fumarate, maleic anhydride and a mixed solution of hydrothermally treated lignin to the above esterification product, mix and mix well to obtain a mixed monomer liquid; then drop all the initiator solution into the mixed monomer liquid; after the dropwise addition is completed, carry out a heat-insulating reaction at 80-90° C. for 3-6 hours, and then cool naturally to room temperature to obtain a mixed solution A; the mixed solution A is subjected to a post-process treatment to obtain a modified copolymer.

3. A hydrogen peroxide efficient water treatment agent according to claim 2, characterized in that: In step A1, the inhibitor is hydroquinone and the catalyst is p-toluenesulfonic acid; the amounts of acrylic acid monomer, allyl polyoxyethylene ether, inhibitor and catalyst are 20-30g: 50-60g: 0.15-0.2g: 1.5-2g.

4. A hydrogen peroxide efficient water treatment agent according to claim 2, characterized in that: In step A2, the initiator is ammonium persulfate, and the amount of the initiator and deionized water is 5-10g:50mL; the amount ratio of methyl fumarate, maleic anhydride and the lignin mixed solution after hydrothermal treatment is 10-15g:10-20g:20-30mL; the post-process treatment is: adding NaOH solution dropwise to the reactor to adjust the pH value of the mixed solution to 7-9.

5. A hydrogen peroxide efficient water treatment agent according to claim 2, characterized in that: In step A2, the method for preparing the hydrothermally treated lignin mixed solution comprises the following steps: The lignin fiber is ground to obtain lignocellulose powder; 30-50g of lignocellulose powder and 500g of distilled water are added into a reactor, and the pressure value of the reactor is set to 0.15-0.25MPa; the reactor is heated from room temperature to 190-200°C, and then kept at this temperature for 30-60min to obtain a hydrothermally treated lignin mixed solution.

6. The preparation process of a hydrogen peroxide high-efficiency water treatment agent according to claim 1, characterized in that: In step B1, the usage ratio of silica gel and deionized water is 2-5g:20-30mL; the frequency of ultrasonic treatment is 20-30KHz; in step B2, the usage ratio of hydrogen peroxide-modified activated carbon powder, ferrosoferric oxide, liquid paraffin, Span 80 and glutaraldehyde is 5-10g:0.2-0.5g:20mL:1-2g:2-5mL.

7. The preparation process of a hydrogen peroxide high-efficiency water treatment agent according to claim 1, characterized in that: In step B2, the hydrogen peroxide-modified activated carbon powder is prepared by the following steps: The activated carbon is ball-milled to obtain activated carbon powder; the activated carbon powder and hydrogen peroxide solution are mixed for reaction at a reaction temperature of 60-70°C for a reaction time of 2-3 hours, and then filtered to obtain hydrogen peroxide-modified activated carbon powder.

8. The process for preparing a hydrogen peroxide efficient water treatment agent according to claim 7, characterized in that: The ball milling speed is 100-200 r / min, and the ball milling time is 1-2 h; the dosage ratio of activated carbon powder and hydrogen peroxide solution is 5-10 g:50 mL.

Citation Information

Patent Citations

  • Method for preparing polymeric ferric sulfate from waste sulfuric acid containing 2-cyan-4-nitroaniline, and application of polymeric ferric sulfate

    CN109928474A

  • Method for preparing polystyrene microsphere-type cellulose-based heavy metal adsorbent

    AU2020101319A4

  • Method for recovering polyether from waste metal processing liquid and application of polyether in concrete slump retaining agent

    CN102174212A